International comparison of the relationship of chronic kidney disease prevalence and ESRD risk - Hallan, Stein I; Coresh, Josef; Astor, Brad C; Asberg, Arne; Powe, Neil R; Romundstad, Solfrid; Hallan, Hans A; Lydersen, Stian; Holmen, Jostein (Journal of the American Society of Nephrology, 2006)
ESRD incidence is much lower in Europe compared with the United States. This study investigated whether this reflects a difference in the prevalence of earlier stages of chronic kidney disease (CKD) or other mechanisms. CKD prevalence in Norway was estimated from the population-based Health Survey of Nord-Trondelag County (HUNT II), which included 65,181 adults in 1995 through 1997 (participation rate 70.4%). Data were analyzed using the same methods as two US National Health and Nutrition Examination Surveys in 1988 through 1994 (n = 15,488) and 1999 through 2000 (n = 4101). The primary analysis used gender-specific cutoffs in estimating persistent albuminuria for CKD stages 1 and 2. ESRD rates and other relevant data were extracted from national registries. Total CKD prevalence in Norway was 10.2% (SE 0.5): CKD stage 1 (GFR >90 ml/min per 1.73 m2 and albuminuria), 2.7% (SE 0.3); stage 2 (GFR 60 to 89 ml/min per 1.73 m2 and albuminuria), 3.2% (SE 0.4); stage 3 (GFR 30 to 59 ml/min per 1.73 m2), 4.2% (SE 0.1); and stage 4 (GFR 15 to 29 ml/min per 1.73 m2), 0.2% (SE 0.01). This closely approximates reported US CKD prevalence (11.0% in 1988 through 1994 and 11.7% in 1999 through 2000). The relative risk for progression from CKD stages 3 or 4 to ESRD in US white patients compared with Norwegian patients was 2.5. This was only modestly modified by adjustment for age, gender, and diabetes. Age and GFR at start of dialysis were similar, hypertension and cardiovascular mortality in the populations were comparable, but US white patients were referred later to a nephrologist and had higher prevalence of obesity and diabetes. In conclusion, CKD prevalence in Norway was similar to that in the United States, suggesting that lower progression to ESRD rather than a smaller pool of individuals at risk accounts for the lower incidence of ESRD in Norway.